2020
DOI: 10.3390/pharmaceutics12060502
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Vesicles Loaded with an HIV-1 Fusion Inhibitor Peptide as a Potential Microbicide

Abstract: The effective use of fusion inhibitor peptides against cervical and colorectal infections requires the development of sustained release formulations. In this work we comparatively study two different formulations based on polymeric nanoparticles and lipid vesicles to propose a suitable delivery nanosystem for releasing an HIV-1 fusion inhibitor peptide in vaginal mucosa. Polymeric nanoparticles of poly-d,l-lactic-co-glycolic acid (PLGA) and lipid large unilamellar vesicles loaded with the inhibitor peptide wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…In our hands, the design of novel amphiphilic peptides made it possible to obtain peptide structures capable of self-assembly in aqueous solution, favoring the solubility of lipopeptides, based on the E1P47 sequence, which are highly hydrophobic and would be highly insoluble under physiological conditions. So far, we have studied the possible administration of entry inhibitor peptides incorporated into drug delivery systems such as liposomes or polymeric nanoparticles. In the present work, we have designed an amphiphilic peptide with anti-HIV-1 activity that is capable of forming self-assembled nanostructures that could allow the administration of the inhibitor peptide without the need of its incorporation into a delivery vehicle.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our hands, the design of novel amphiphilic peptides made it possible to obtain peptide structures capable of self-assembly in aqueous solution, favoring the solubility of lipopeptides, based on the E1P47 sequence, which are highly hydrophobic and would be highly insoluble under physiological conditions. So far, we have studied the possible administration of entry inhibitor peptides incorporated into drug delivery systems such as liposomes or polymeric nanoparticles. In the present work, we have designed an amphiphilic peptide with anti-HIV-1 activity that is capable of forming self-assembled nanostructures that could allow the administration of the inhibitor peptide without the need of its incorporation into a delivery vehicle.…”
Section: Discussionmentioning
confidence: 87%
“…So far, we have studied the possible administration of entry inhibitor peptides incorporated into drug delivery systems such as liposomes or polymeric nanoparticles. 42 45 In the present work, we have designed an amphiphilic peptide with anti-HIV-1 activity that is capable of forming self-assembled nanostructures that could allow the administration of the inhibitor peptide without the need of its incorporation into a delivery vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Niosomes, the non-ionic surfactant based liposome alike organic nanovesicle are getting popular in the advanced biomedical sciences considering their non-immunogenicity and stable optical properties, which make them a suitable carrier of both hydro/lipophilic drug molecules. Excellent bioavailability and controlled release of specific drugs at the targeted sites make such nanocarriers ideal antiviral agents (HSV-1 virus), where nano-niosome was loaded with suitable antiviral drug (acyclovir) ( Sánchez-López et al, 2020 ). Improved drug delivery mechanism and suitable drug release kinetics may allow such nanocarriers to be used in infectious virus diseases (nanomicelles) ( Fig.…”
Section: Mode Of Action and Biomedical Applications Of Biocompatible mentioning
confidence: 99%
“…Sánchez–López et al prepared suitable delivery nanocarriers for releasing HIV-1 fusion inhibitor peptide in vaginal mucosa: polymeric NPs of PLGA and lipid large unilamellar vesicles loaded with the inhibitor peptide [ 67 ]. The authors comparatively studied both systems and found high entrapment efficiency of the inhibitor peptide in lipid vesicles, which was understood because of the hydrophobic nature of the peptide.…”
Section: Nanotechnology Approaches For Prevention Of Hiv Infectionmentioning
confidence: 99%